Labour Supply and Inequality Effects of In-Work Benefits: Evidence from Serbia - Sunčica Vujić; Saša Ranđelović; Jelena Žarković Rakić; Marko Vladisavljević (Naše gospodarstvo/Our economy, 2019)
Low labour market participation, together with the high effective tax wedge at low wage levels, create a fertile ground for the introduction of the in-work benefits (IWB) in Serbia. Our paper provides an ex-ante evaluation of the two IWB schemes, directed at stimulating the labour supply and more equal income distribution. The methodological approach combines the tax-and-benefit microsimulation model with the discrete labour supply model. Our results show that both individual and family-based IWB schemes would considerably boost labour market participation, although family-based benefits would have disincentivizing effects for the secondary earners in couples. Most of the behavioural changes take place among the poorest individuals, with significant redistributive effects.